Islam and Counseling: Model of Practice in Matrilineal System of The Minangkabau Culture - Yusri, Fadhilla; Afrida, Yeni (Universitas Muhammadiyah Metro, 2020)
Islam and counseling are two things that actually support each other in their practice. Islam states that counseling is a way to help each other between humans. Meanwhile, counseling uses Islam as an approach in counseling services. The Minangkabau community is one of the societies with a very strong Islamic maternal lineage. The purpose of this study was to reveal the appropriate counseling approach for use in the Minangkabau community with all its peculiarities. This research is a library research, where the data required in the research are obtained through analysis of various literatures in the library. Based on the results of the study, it was revealed that in the matrilineal community in Minangkabau, counseling was still new and not very familiar. The material society in Minangkabau has a philosophy of life